Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the Czech Republic's monetary policy after removal of the exchange rate floor. The koruna-euro exchange rate floor, which had been in place for more than three years, was eliminated in the beginning of the second quarter of 2017. Exit poses a number of challenging policy questions, including on the optimal monetary policy in its aftermath. The simulations indicate that a monetary policy response that is ex-post too loose is likely to be less costly than a monetary policy response that is ex-post too tight. This suggests that a gradual approach to interest rate increases is advisable.